1975
DOI: 10.1042/bj1520379
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial protein turnover by thyroid hormone(s)

Abstract: 1. The effect of thyroidectomy on turnover rates of liver, kidney and brain mitochondrial proteins was examined. 2. In the euthyroid state, liver and kidney mitochondria show a synchronous turnover with all protein components showing more or less identical half-lives compared with the whole mitochondria. The brain mitochondrial proteins show asynchronous turnover, the soluble proteins having shorter half-lives. 3. Mitochondrial DNA (m-DNA) of liver and kidney has half-lives comparable with that of whole mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
(40 reference statements)
3
20
0
Order By: Relevance
“…In accordance with other research, which have shown that thyroid hormone exerts dif ferent effects on the turnover and content of mit-DNA and protein of different tissues [28,29], the modifications with thyroid state of heart mit-NA levels differ from those found in liver. Particularly the comparison of the present findings with our previously pub lished data [2.…”
Section: It Has Been Known For Many Years That Thysupporting
confidence: 92%
“…In accordance with other research, which have shown that thyroid hormone exerts dif ferent effects on the turnover and content of mit-DNA and protein of different tissues [28,29], the modifications with thyroid state of heart mit-NA levels differ from those found in liver. Particularly the comparison of the present findings with our previously pub lished data [2.…”
Section: It Has Been Known For Many Years That Thysupporting
confidence: 92%
“…Therefore, the T 3 -induced decrease in the ability of mitochondria to withstand oxidative challenge could be one of the mechanisms responsible for the acceleration of the mitochondrial protein turnover by thyroid hormone [37,38]. If so, T 3 treatment should be associated with an altered distribution of the mitochondrial population into the three fractions, because the degradation processes should be greater in the M 1 fraction, exhibiting higher cytochrome content and lower antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters such as the total content of proteins [24], the turnover of whole mito chondria and their different protein compo nents [25], the mitochondrial respiration [8], the development of mitochondrial mem branes [26], the levels of mitochondrial en zymes [27,28] are differentially affected by thyroid hormone in different tissues. These results suggest that a physiological serum level of thyroid hormone is required to maintain ratios, between mitochondrial and other cel lular compartments or between different pro tein components of mitochondria, suitable for the tissue function.…”
Section: Discussionmentioning
confidence: 99%